D-pinitol modulates the anti-emetic effects of aprepitant, domperidone, and ondansetron in chicks - Md. Elit Rahman; Md. Anisur Rahman; Salehin Sheikh; Md. Jannatul Islam Polash; Sozoni Khatun; Mst. Sonia Akter Bristi; Md. Showkoth Akbor; Mst. Farjanamul Haque; Mehedi Hasan Bappi; Tohidul Islam Tanim; Siddique Akber Ansari; Irfan Aamer Ansari; et al. (Pharmaceutical Science Advances)
Naturally occurring substance, D-pinitol (DPL) belongs to the significant inositol family has numerous pharmacological activity. In this study we evaluated the anti-emetic effect as well as modulation activities of DPL on the recent market drugs aprepitant (APR), domperidone (DOM), hyoscine butyl bromide (HYS), and ondansetron (ODN) on emesis in the chick model. To highlight the possible anti-emetic activity in copper sulfate induced emesis chick models, we use several reference drugs, such as APR (26 ​mg/kg), DOM (7 ​mg/kg), OND (5 ​mg/kg), and HYS (21 ​mg/kg), as positive controls, while the vehicles serve as negative controls. All reference drugs are given alone or in combined groups to evaluate their anti-emetic and modulation effects. The results suggest DPL (25 or 50 ​mg/kg) increases the mean number of latency in the chicks compared to vehicles, and the combination groups, DPL (25 ​mg/kg) showed better anti-emetic effects with DOM and ODN while DPL (50 ​mg/kg) reduces the number of retches compared to vehicles and combined drug therapy with reference drugs. Additionally, A variety of computational algorithms were used to visualise ligand–receptor interactions and quantify the binding affinities of DPL and other ligands towards the dopamine receptors (D2 and D3), muscarinic acetylcholine receptors (M1–M5), and serotonin receptor (5HT3). The molecular docking study indicated that DPL exhibits the highest binding affinity towards subtypes M2 (having a docking score of −5.7 ​kcal/mol) and D3 (having a docking score of −5.7 ​kcal/mol) in comparison to certain standards for these receptors, which have docking scores of DOM (−9.7 ​kcal/mol) and HYS (−7.1 ​kcal/mol) for M2 and D3, respectively. Our findings suggest that DPL has anti-emetic properties in chicks, possibly through interactions with the M2 and D3 receptor pathways.